In situ electrochemical EPR studies of charge transfer across the liquid/liquid interface - Webster, R; Dryfe, R; Coles, B; Compton, R (1998)
The in situ measurement of EPR spectra of radical ions generated at the polarized liquid/liquid interface is described in relation to the 7,7,8,8-tetracyanoquinodimethane (TCNQ), 2,3,5,6-tetrachloro-p-benzoquinone (TCBQ), and 2,3,5,6-tetrafluoro-p-benzoquinone (TFBQ) radical anions and the tetrathiafulvalene (TTF) radical cation. TCNQ and TTF were chosen as model compounds with which to quantify the performance of a novel liquid/ liquid electrochemical EPR cell. The anion radical of TCNQ and the cation radical of TTF in 1,2-dichloroethane (DCE) were produced at the water interface by electron transfer from/to the aqueous-phase ferricyanide/ferrocyanide redox couple by applying a potential difference between the two phases with a four-electrode potentiostat. The EPR signal intensity (at constant magnetic field) of the resultant organic radicals was monitored during potential step experiments which indicated that the EPR data could be modeled in terms of diffusional transport. TCBQ and TFBQ were chosen as compounds to model the electron transfer behavior of biologically important quinones at the oil/water interface. The EPR and voltammetric data obtained from TCBQ/TCBQ-· and TFBQ/ TFBQ-· indicated unambiguously that the two semiquinones are stable at the DCE/water interface and do not undergo immediate protonation.